Determinants of CO2 emissions in the ASEAN Economies: The Role of Renewable and Non-renewable Energy - Nawab, Tabish; Aamir, Muhammad Faizan (iRASD Journal of Economics, 2020)
According to the literature of energy-growth-environment, a numeral of studies aims to recognize the factors of CO2 (carbon dioxide) emissions resulting from significant increases in CO2 emissions in recent decades. The selection of data is the main criticism connected to the present literature. Most of the studies used the overall consumption of energy, and other criticism concerns selecting panel assessment techniques. Nearly all the previous research used general panel approaches that overlooked long term dependence. This empirical study fills the gap revealed in the past studies of the effect of trade openness, income, non-renewable and renewable energy on carbon emissions in the presence of EKC (Kuznets environmental curve) for the ASEAN economies from the time spam 2000 to 2018 using panel ARDL, Pooled Mean Group (PMG) estimation techniques. The results of the PMG estimator confirm the presence of the EKC hypothesis in selected ASEAN countries. Furthermore, Trade and renewable energy minimize carbon dioxide emissions, whereas non-renewable upsurges CO2 emissions. The outcomes also revealed cointegration amongst carbon emissions and renewable energy and one-way causation found from income to CO2 productions, non-renewable energy to carbon emissions, and trade openness toward carbon dioxide emissions. Moreover, it concluded that ASEAN states that the government should advise the industries and all sectors to modify their energy sources from non-renewable energy sources to renewable energy sources. Because it helps to increase the level of energy and economic growth in reducing the carbon emission level.